ENHANCING STUDENTS’ ENGAGEMENT USING INTERACTIVE APPLICATIONS IN ONLINE LECTURES - Prattama Santoso Utomo; Muhamad Reza Utama (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Online lectures are now increasing in popularity for medical education worldwide. Online lectures were reported effective and efficient and might facilitate a safe learning environment with physical distancing during the COVID-19 pandemic. To date, there is a range of online meeting applications available, namely, Zoom®, GoogleMeet®, Webex®, and many others. The main challenge of online lectures is ensuring students’ engagement throughout the learning activity. Lecturers possess lower control of the class environment online than face-to-face activities. Passive students are also another barrier and concern. This article reviews the use of quizzes and online surveys as interactive applications to increase students’ engagement during online lectures, for instance, Zoom® Polls and Mentimeter ®.Learning Media Review: Zoom® Polls is easy for quizzes and surveys to complement Zoom® meetings. The polls can be used synchronously for large and small-class activities. Meanwhile, Mentimeter® also has a quiz, survey and word cloud as interactive activities during online lectures. Mentimeter® is a web-based application in which the free version allows access to most of its features. The utilization of interactive applications should be carefully prepared to ensure good student engagement but not overly used to prevent possible distractions. Instructions and question items should be made clear and thorough.Conclusion: Survey and interactive presentation applications are offered to present better class and online lecture engagement